Use of meijer’s g-function and bessel functions in electrical network theory (1994)
In this paper we have obtained a solution of the classical time-domain synthesis problem occuring in electrical network theory in a series of Bessel functions. We have also obtained a particular solution of the problem involving Meijer's G-function and Bessel functions.